2019
DOI: 10.3389/fpsyg.2019.02421
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Speech Recognition in Noise in Children: Effects of Hearing Status and Vocabulary

Abstract: Objectives: The aims of the current study were: (1) to compare growth trajectories of speech recognition in noise for children with normal hearing (CNH) and children who are hard of hearing (CHH) and (2) to determine the effects of auditory access, vocabulary size, and working memory on growth trajectories of speech recognition in noise in CHH.Design: Participants included 290 children enrolled in a longitudinal study. Children received a comprehensive battery of measures annually, including speech recognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 65 publications
(121 reference statements)
4
21
0
Order By: Relevance
“…Regarding the effects of age, this study confirmed that younger children struggle more to understand speech in noise compared with older ones. This is consistent with a large body of research comparing the effects of noise on younger versus older children (e.g., Johnson, 2000; Soli & Sullivan, 1997; Walker et al., 2019; Werner & Boike, 2001), and can be traced back to developmental changes in terms of language skills of school-age children (e.g., Firmansyah, 2018). At a more general level, this finding implies that since younger children understand speech especially poorly in noisy environments it is particularly important to provide classrooms with good acoustical conditions for them.…”
Section: Discussionsupporting
confidence: 85%
“…Regarding the effects of age, this study confirmed that younger children struggle more to understand speech in noise compared with older ones. This is consistent with a large body of research comparing the effects of noise on younger versus older children (e.g., Johnson, 2000; Soli & Sullivan, 1997; Walker et al., 2019; Werner & Boike, 2001), and can be traced back to developmental changes in terms of language skills of school-age children (e.g., Firmansyah, 2018). At a more general level, this finding implies that since younger children understand speech especially poorly in noisy environments it is particularly important to provide classrooms with good acoustical conditions for them.…”
Section: Discussionsupporting
confidence: 85%
“…Tomblin et al (2015) found that children who wore hearing aids for at least 10 hours/day during the preschool years had stronger language growth trajectories than peers who wore hearing aids for less than 10 hours/day. More recently, Walker et al (2019) showed that children with higher amounts of auditory dosage, a measure that combines both a child’s aided audibility for speech sounds and their device use, had better sentence recognition than peers with lower auditory dosage. Consistent auditory access, as measured by hours of device use, predicts individual differences in language and speech perception outcomes for CHL.…”
Section: Introductionmentioning
confidence: 99%
“…Classrooms are an example of environments where children are subject to noise exposure [3][4][5][6] and where ASR technology is increasingly used in education. The degradation of ASR systems in recognition of noisy children's speech depends on many issues such as noise type, signal-to-noise ratio (SNR), acoustic and linguistic differences in fundamental frequency (F 0 ), speaking rate, and formant frequencies between adult and child speech [7][8][9][10][11][12][13][14][15][16]. Decreased ASR performance of children's speech compared to adults' speech is also explained by the fact that the number of publicly available training data for children's speech (tens of hours) [17,18] is much smaller compared to that of adults' speech (thousands of hours) [19,20].…”
Section: Introductionmentioning
confidence: 99%